2019
DOI: 10.1101/724419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptation is influenced by the complexity of environmental change during evolution in a dynamic environment

Abstract: The environmental conditions of microorganisms' habitats may fluctuate in unpredictable ways, in terms of temperature, carbon source, pH, and salinity to name but a few. Such environmental heterogeneity presents a challenge for such microorganisms, as they have to adapt not only to be fit under a specific condition, but they must also be robust across many conditions and be able to deal with the switch between conditions itself. While experimental evolution has been used for decades to gain insight into the ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…For instance, the stochastic variance in selection coefficients over one generation (or infinitesimal time step in continuous time) can be used to predict evolutionary outcomes over multiple generations, such as probabilities of fixation [27,29] or expected heterozygosities [28], analogously to the influence of effective population size for genetic drift. However, while the demographic consequences of the magnitude and autocorrelation of environmental variations have been experimentally explored [35][36][37][38], and evolutionary experiments have been performed under randomly changing environments [39][40][41][42][43], we are not aware of attempts to measure the stochastic variance of population genetic change under conditions where patterns of random environmental fluctuations have been experimentally manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the stochastic variance in selection coefficients over one generation (or infinitesimal time step in continuous time) can be used to predict evolutionary outcomes over multiple generations, such as probabilities of fixation [27,29] or expected heterozygosities [28], analogously to the influence of effective population size for genetic drift. However, while the demographic consequences of the magnitude and autocorrelation of environmental variations have been experimentally explored [35][36][37][38], and evolutionary experiments have been performed under randomly changing environments [39][40][41][42][43], we are not aware of attempts to measure the stochastic variance of population genetic change under conditions where patterns of random environmental fluctuations have been experimentally manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evolution experiments selecting for azole resistance have demonstrated that this paradigm can identify new resistance factors and can validate candidate secondary antifungals that prevent resistance evolution (e.g. Cowen et al 2000, Anderson et al 2003, Selmecki et al 2009, Hill et al 2013, Boyer et al 2021. We anticipated that additional replicates carried out with different culturing protocols would lead to the identification of novel resistance factors.…”
Section: Introductionmentioning
confidence: 99%
“…We worked with the halotolerant micro-alga Dunaliella salina, which can thrive across a broad range of salinities. Contrary to previous experiments that also focused on random variation in the environment (Boyer et al, 2021;Dey et al, 2016;Wieczynski et al, 2018), we here allowed salinity to vary over a continuous range (rather than switching randomly from low to high), with a controlled distribution over time. We used a liquid-handling robot to control the mean, variance, and autocorrelation of salinity, and tracked the frequency of standing genetic variants through time by Illumina amplicon sequencing.…”
Section: Introductionmentioning
confidence: 99%